Establishing a Model for Free Dental Care for Uninsured Patients Served by a Student-Run Clinic - Nguyen, Eliza; Stewart, Heather; Maldonado, Marissa; Cook, Elizabeth; Arboleda, Bianca; Simoneit, Elizabeth; Palakurty, Sri Harsha; Shahin, Alexander; Gonzalez, Eduardo (Journal of Student-Run Clinics, 2021)
Background: This paper details the establishment of a free dental clinic within the Building Relationships and Initiatives Dedicated to Gaining Equality (BRIDGE) Healthcare Clinic, a student-run free clinic, in Hillsborough County, Florida through collaboration with Hope in Health Project (HHP), and local dental volunteers. The purpose of the clinic is to provide general dental service to BRIDGE patients. It notes the patient demographics, procedure types, and total cost of care provided at the first dental clinic. Methods: Nine dentists, two dental hygienists, and one dental assistant were recruited through HHP as well as 29 local volunteers to participate in the clinic. BRIDGE Clinic patients were contacted via text message informing them of the opportunity to receive dental care. A triage event was held for initial evaluation and to determine services needed. The following week, triaged patients returned to receive dental services. Procedures offered included prophylaxis with fluoride varnish, extractions, and fillings. Results: 71 patients were triaged and 62 received a procedure. The average age was 49Â±10 years. Of patients triaged, 87% (62) received at least one procedure, 72% (51) received prophylaxis with varnish, 18% (13) received extractions, and 39% (28) received fillings. Total number of procedures completed was 126, which included 51 prophylaxis, 28 extractions, and 47 fillings. The total cost for the services provided was 31,065 United States Dollar (USD) with an average cost per patient of 438 USD. Conclusion: This project demonstrates the successful implementation of a pilot free dental clinic in the context of an established free, primary healthcare clinic. It provides information on the structure and cost of a free dental clinic and how it can be implemented to provide dental care to uninsured patients.